2011
DOI: 10.1007/s11999-011-1792-3
|View full text |Cite
|
Sign up to set email alerts
|

High Revision Rate at 5 Years after Hip Resurfacing with the Durom Implant

Abstract: Background/rationale There is growing evidence that different resurfacing implants are associated with variable survival and revision rates. A registry analysis indicated the Durom resurfacing implant had high revision rates at 5 years, whereas three original studies reported low revision rates at short-term followups. Thus, the revision rates appear controversial. Questions/purposes We therefore assessed (1) the survivorship including differences between women and men at a mean of 5 years after resurfacing wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…Thus it seems that for a young population, the survival rate for a resurfacing implant is very close to that of a traditional THA, which is consistent with data from our series (5-year rate between 90 and 100%, depending on the centre). But this rate was worse because of complications specific to the Durom implant, such as early implant tilting [27], which was observed in 1% of cases with this same implant [34]. This occurred more often than with the Birmingham hip resurfacing system because the bone ingrowth is not as good [27].…”
Section: Discussionmentioning
confidence: 99%
“…Thus it seems that for a young population, the survival rate for a resurfacing implant is very close to that of a traditional THA, which is consistent with data from our series (5-year rate between 90 and 100%, depending on the centre). But this rate was worse because of complications specific to the Durom implant, such as early implant tilting [27], which was observed in 1% of cases with this same implant [34]. This occurred more often than with the Birmingham hip resurfacing system because the bone ingrowth is not as good [27].…”
Section: Discussionmentioning
confidence: 99%
“…1,20 Inferior results with specific implant systems have also been shown in various studies. 3,7,[30][31][32][33] Higher rates of failure were noted with the ASR, Durom and Cormet systems. Our study was not designed specifically to compare the systems, but appears to be in keeping with the published global experience.…”
Section: Discussionmentioning
confidence: 97%
“…5 Several studies have reported successful mid-term survival rates for four different resurfacing systems: Birmingham Hip Resurfacing (BHR; Smith & Nephew, Memphis, Tennessee), 12,[21][22][23][24] Cormet 2000 (Corin, Tampa, Florida), 25,26 Conserve Plus (Wright Medical Technologies, Memphis, Tennessee) 27,28 and the Recap-Magnum (Biomet, Warsaw, Indiana). 29 Two other hip resurfacing systems, the Durom (Zimmer, Warsaw, Indiana) 30,31 and the Articular Surface Replacement (ASR) (DePuy, Warsaw, Indiana), 7,32,33 have been recalled owing to unacceptable design-related failure rates.…”
Section: -3mentioning
confidence: 99%
“…A recent study [32] of the Durom 1 resurfacing system reported a 17% revision rate in women and 9% in men at a mean followup of 5 years, of which more than 1 .…”
Section: Discussionmentioning
confidence: 98%
“…Recently high failure rates have been reported with certain metal-metal (MM) hip resurfacing implants [4,22,32]. However, well-designed and properly positioned hip resurfacing implants continue to show 96% to 98% survival The institution of one or more of the authors (JD, CP, HZ, DM) has received funding from Smith & Nephew Orthopaedics UK Ltd (Warwick, UK).…”
Section: Introductionmentioning
confidence: 99%